2016
DOI: 10.1177/1526602816656355
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Outcomes of the Nellix Endovascular Aneurysm Sealing System

Abstract: The use of the Nellix device in everyday clinical practice is safe and offers promising midterm results. The risk of secondary aortoenteric fistula requires further analysis. Longer follow-up is needed to assess the actual efficacy of the device, although the risk of migration with late endoleak seems low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 15 publications
0
35
2
Order By: Relevance
“…Technical success was reported by 13 studies (1,233 patients) 815,1721. The technical success rate ranged from 98% to 100%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Technical success was reported by 13 studies (1,233 patients) 815,1721. The technical success rate ranged from 98% to 100%.…”
Section: Resultsmentioning
confidence: 99%
“…All 14 articles were single-arm observational studies and were published after 2011. The recruitment period in all but one study was 1 year or more 17. Four studies10,12,13,16 reported 1-year outcomes, while the remaining studies reported longer follow-up outcomes 8,9,11,14,15,1821.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Endovascular aneurysm sealing (EVAS) is a welldescribed technique to treat aortic aneurysms using the Nellix EVAS system (Endologix Inc, Irvine, CA, USA). 13,14 Nellix consists of 2 balloon-expandable chromium-cobalt stents surrounded by polytetrafluoroethylene endobags that are filled with biocompatible polymer to seal proximally and distally and also occupy the aneurysm flow lumen. This mechanism vs the circumferential radial force of a conventional aortic stent-graft makes EVAS appropriate for treating paravisceral aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…The 1-year estimates for freedom from secondary intervention and from any endoleak were 92% and 95%, respectively. Silingardi et al 4 concurrently reported the first midterm outcomes of 65 EVAS patients treated at 2 centers; their estimated 18-month freedom from secondary interventions was 95%.…”
Section: Introductionmentioning
confidence: 99%